2019
DOI: 10.1093/annonc/mdz097.006
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of metastases detected on a staging CT scan prior to neoadjuvant chemotherapy in early stage breast cancer

Abstract: Background: With the increased use of neoadjuvant chemotherapy (NAC), as well as increasing efficacy of systemic therapy, a substantial proportion of clinically nodepositive patients may achieve a nodal pathologic complete response (pCR) with chemotherapy. Instead of axillary lymph node dissection (ALND), a novel surgical technique called targeted axillary dissection (TAD) including removal of sentinel lymph nodes (SLNs) and clip-marked node has been gaining acceptance in recent years. Logically, preoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A recent analysis of 204 patients with stage I or II breast cancer who underwent staging with CT and/or MRI and/or bone scan identified lymph node involvement and stage IIb disease as risk factors for an increased incidence of distant metastases 19 . An abstract 26 published in 2019 reported a 10 per cent incidence of distant disease among 163 patients selected for neoadjuvant chemotherapy who underwent staging CT, as well as a correlation between increasing T category and metastatic disease in patients with clinically node-negative disease. Two other studies 27 , 28 also found similar significant correlations between the presence of metastatic disease and increasing tumour size and nodal involvement.…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis of 204 patients with stage I or II breast cancer who underwent staging with CT and/or MRI and/or bone scan identified lymph node involvement and stage IIb disease as risk factors for an increased incidence of distant metastases 19 . An abstract 26 published in 2019 reported a 10 per cent incidence of distant disease among 163 patients selected for neoadjuvant chemotherapy who underwent staging CT, as well as a correlation between increasing T category and metastatic disease in patients with clinically node-negative disease. Two other studies 27 , 28 also found similar significant correlations between the presence of metastatic disease and increasing tumour size and nodal involvement.…”
Section: Introductionmentioning
confidence: 99%